PEGADAIAN SYARI’AH: (Teori dan Prakteknya di Indonesia) - Suryani, Eli (Alhurriyah, 2009)
One of alternative ways in Islamic financing is by using pawnshop, it is did not need for any difficult requirement even with the process. That is why an institution of Islamic pawnshop has social functions (besides it indicates of business function) towards society benefits as ta’awun (helpful) concept in Islam. But we still need for a review study related with the all transactions and practicalities in the Islamic pawnshop. Practically and operationally, an Islamic pawnshop is more taking part in economic aspect and profits oriented. Only a few of them would be orient in social aspect. The most basic ideology of a pawnshop (rahn) is for tabarru’ (goodness) and not for tijarah (trade).